A Study on the Influence of Bulbous bow on the Resistance of Fishing Vessel Hull form Using CFD Analysis - M. V. Baiju; Vipinkumar; Dhijudas P. H; K. Sivaprasad; Leela Edwin (Fishery Technology, 2022)
Bulbous bow forms have a significant effect on the ship resistance components and are today an integral part of many ship designs. The hydrodynamic effect of the bulbous bow is based on the change of flow distribution around the bow, creating waves that interfere with the waves created by the hull, improving the flow around the bow. A properly designed bulb affects nearly all the hydrodynamic properties of the ship. The advancements in structural hydrodynamics is limited in Indian fishing industry and mechanised fishingvessels are not fitted with bulbous bows. This study illustrates the influence of bulbous bow on the resistance of fishing vessels. Computational Fluid Dynamics (CFD) analysis was used for optimisation of ship hull forms, full-scale predictions, and to appraise physical effects of bulbous bow. Geometrical 3D modelling of three reference hull forms namely conventional hull form, hull form with oval type bulbous bow and hull form with Nabla type bulbous bow created using Maxsurf software was chosen to perform test cases to evaluate the influence. Experimental data of three reference hull forms were collected for validation with results of CFD software. The CFD numerical setup stages were illustrated to estimate resistance components such as viscous resistance and wave making resistance. The mesh independency study of hull models were created with results of previous numerical studies. The comparison between the reference hull models and bulbous bow models show the amount of reduction in wave making resistance due to fittingof bulbous bow. The Nabla type hull form gave eduction in drag compared to the conventional hull form.